2005
DOI: 10.1124/mol.105.011254
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Inhibits Expression of Vascular Endothelial Growth Factor and Angiogenesis in Human Lung Cancer Cells: Implication of Chemoprevention of Lung Cancer

Abstract: Apigenin is a natural dietary flavonoid. It has recently been shown to have anticancer effects on prostate and ovarian cancer cells. However, the molecular basis of the effect of apigenin on cancer cells remains to be elucidated. In this study, we found that apigenin inhibited A549 lung cancer cell proliferation and vascular endothelial growth factor (VEGF) transcriptional activation in a dose-dependent manner. In an attempt to understand the mechanism of apigenin-inhibited VEGF expression, we found that apige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
115
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(127 citation statements)
references
References 62 publications
(62 reference statements)
11
115
0
1
Order By: Relevance
“…Epidemiological data suggest that consumption of plant flavonoids may be associated with a decreased risk of lung cancer. Liu et al (98) have shown that apigenin inhibited A549 lung cancer cell proliferation and vascular endothelial growth factor (VEGF) transcriptional activation in a dosedependent manner. Apigenin inhibited VEGF transcriptional activation through the HIF-1 binding site, and specifically decreased HIF-1·, but not HIF-1ß subunit expression in these cells.…”
Section: Apigenin and Leukemiamentioning
confidence: 99%
“…Epidemiological data suggest that consumption of plant flavonoids may be associated with a decreased risk of lung cancer. Liu et al (98) have shown that apigenin inhibited A549 lung cancer cell proliferation and vascular endothelial growth factor (VEGF) transcriptional activation in a dosedependent manner. Apigenin inhibited VEGF transcriptional activation through the HIF-1 binding site, and specifically decreased HIF-1·, but not HIF-1ß subunit expression in these cells.…”
Section: Apigenin and Leukemiamentioning
confidence: 99%
“…In 11 days, the Matrigel plugs were removed from the mice and trimmed of the surrounding tissues. Hemoglobin content of the gel plug was measured as described (31). The data represented the mean F SD (n = 8) from two independent experiments.…”
Section: In Vivo Angiogenesis Assaymentioning
confidence: 99%
“…Tumor angiogenesis was done as described previously (31). In brief, DU145 cells were mixed with Matrigel at a ratio of 1:2 (v/v, %), in the presence or absence of chrysin (30 Amol/L); 0.45 mL of the mixture (total cell number = 3 Â 10 6 ) was injected s.c. into the flank sides of BALB/c-nu nude mice (male, 4 weeks old, purchased from Shanghai Experimental Animal Center, Shanghai, China).…”
Section: In Vivo Angiogenesis Assaymentioning
confidence: 99%
“…Flavonoids and isoflavonoids have potent antioxidant activity relavent to cancer. 50,51) Glycoside linked flavonoids are responsible for antioxidant effects. 43) Isoflavonoids play an important role in prevention of breast cancer, prostrate cancer and atherosclerosis.…”
Section: Resultsmentioning
confidence: 99%